2011
DOI: 10.1007/s00066-011-1129-x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of hemoglobin level and other factors in patients with high-grade gliomas treated with postoperative radiochemotherapy and sequential chemotherapy based on temozolomide

Abstract: Our results confirm the impact of well-known prognostic factors on survival. In this research, it was found that a low hemoglobin level before radiotherapy can adversely influence the prognosis of patients with malignant gliomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 37 publications
3
10
0
Order By: Relevance
“…The finding that low hemoglobin level is significantly associated with a lower survival rate of GBM patients is consistent with the known fact that tendency toward anemia is linked to lower survival rates in cancer patients (23,25). In the context of GBM, several works supported low hemoglobin levels as a poor prognostic factor (16)(17)(18)(19)26), though other works were less supportive of this notion. Fiorentino and Fusco (26) studied the effect of hemoglobin level of mostly biopsied elderly GBM patients (median age of 71 years) and found that a hemoglobin level cutoff of ≥12 g/dL was not significantly related to overall survival but did show better progression-free survival.…”
Section: Discussionsupporting
confidence: 76%
See 3 more Smart Citations
“…The finding that low hemoglobin level is significantly associated with a lower survival rate of GBM patients is consistent with the known fact that tendency toward anemia is linked to lower survival rates in cancer patients (23,25). In the context of GBM, several works supported low hemoglobin levels as a poor prognostic factor (16)(17)(18)(19)26), though other works were less supportive of this notion. Fiorentino and Fusco (26) studied the effect of hemoglobin level of mostly biopsied elderly GBM patients (median age of 71 years) and found that a hemoglobin level cutoff of ≥12 g/dL was not significantly related to overall survival but did show better progression-free survival.…”
Section: Discussionsupporting
confidence: 76%
“…It has been somewhat investigated previously with regard to GBM prognosis, e.g., Lutterbach et al (16) pointed to low hemoglobin level as an adverse prognostic factor. This work was supported by subsequent works showing similar results (17,18). Nevertheless, some works failed to demonstrate the significant prognostic value of hemoglobin level for GBM (18,19,26).…”
Section: Introductionsupporting
confidence: 67%
See 2 more Smart Citations
“…Similarly, a previous study showed that the HGB level did not influence clinical outcome in elderly patients with GBM [18]. However, Céfaro et al revealed that a low HGB level was associated with shorter OS in patients with high-grade gliomas [19]. Odrazka et al identified the adverse prognostic effect of low HGB levels on the clinical outcome of GBM [20].…”
Section: Discussionmentioning
confidence: 98%